Low-power attenuation packaging adhesive film, preparation method thereof and photovoltaic module

By grafting charge dissipation agents onto the surface of inorganic nanomaterials, a low-power attenuation encapsulating film was prepared, solving the problem of power attenuation in photovoltaic modules caused by EVA resin hydrolysis. This improved charge conduction and corrosion resistance, reducing the risk of voltage breakdown in photovoltaic modules.

CN121045973APending Publication Date: 2025-12-02CHANGZHOU BAIJIA NIANDAI FILM TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202511316850.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-16
Publication Date
2025-12-02

AI Technical Summary

Technical Problem

During long-term operation, the encapsulating film of existing photovoltaic modules generates free acetic acid due to the hydrolysis of EVA resin, which leads to the PID effect and causes the power of photovoltaic modules to decay. Existing technologies are unable to effectively solve the problems of cell corrosion and power reduction caused by charge migration.

Method used

By grafting charge dissipation agents onto the surface of inorganic nanomaterials to form continuous conductive channels, and combining them with EVA matrix resin and silane coupling agents, a low-power attenuation encapsulation film is prepared to enhance charge conduction and corrosion resistance.

Benefits of technology

It effectively reduces the risk of film delamination, improves the peel strength of the film after aging, increases the durability of charge conduction and corrosion resistance, reduces the risk of voltage breakdown, and reduces the power decay of photovoltaic modules.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121045973A_ABST
    Figure CN121045973A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of packaging adhesive films, and particularly relates to a low-power attenuation packaging adhesive film and a preparation method thereof.The preparation method comprises the following steps that S1, an inorganic nano-material and ethyl alcohol are evenly mixed and subjected to a reflux reaction to form a solution A, a charge dissipation agent and deionized water are mixed to form a solution B, the solution B is added into the solution A, MgCl is added at the same time, the temperature is increased to 60-80 DEG C, and stirring is conducted for 1-2 h; after full reaction, filtering and washing redundant MgCl to obtain the charge dissipater modified inorganic nano material; s2, uniformly mixing EVA matrix resin, a charge dissipater modified inorganic nano material, a silane coupling agent and an initiator according to a ratio, and mixing at 40 DEG C until complete absorption to obtain a base material; s3, the base material is placed in a granulator to be subjected to melt grafting granulation at the temperature of 160-250 DEG C, and after cooling, grain-sized dicing is performed to obtain grafted anti-PID master batches; and S4, blending the grafted anti-PID master batch and an EVA base material according to a certain proportion, and carrying out casting, embossing, cooling and rolling in a screw extruder to obtain the low-power attenuation packaging adhesive film.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of encapsulation film technology, specifically relating to a low-power attenuation encapsulation film and its preparation method, and photovoltaic modules. Background Technology

[0002] As an important component of photovoltaic module encapsulation, encapsulating film provides photovoltaic modules with multiple protections, including optical, physical, insulating, and moisture-proof protection, thereby extending the service life of photovoltaic modules and enabling them to maintain excellent conversion performance under high temperature, high humidity, and strong radiation conditions. Currently, photovoltaic modules encapsulated with photovoltaic film generally exhibit PID (potential-induced degradation) during long-term operation. Under positive and negative voltage operating conditions, leakage current is generated between the encapsulation material and the glass. This, combined with the acetate ions released by the decomposition of EVA resin during aging, causes a continuous decrease in the power of the photovoltaic module, generally exceeding 10%, and in severe cases, reaching around 20%.

[0003] EVA resin is a high-molecular polymer containing vinyl acetate branches, characterized by high adhesion, strong barrier properties, and excellent film formation, and is currently widely used in photovoltaic encapsulation. However, its vinyl acetate branches are highly susceptible to hydrolysis during hydrothermal aging, producing free acetic acid. This free acetic acid reacts with the grid lines on the cell surface under high temperature and moisture conditions, causing corrosion of the grid lines. Simultaneously, the decomposed free acetic acid reacts with Na / K ions on the glass surface under the acceleration of a negative pressure electric field, thus penetrating the passivation layer of the cell and causing blackening of the cell and a sharp drop in power after PID (Power Degradation Processing).

[0004] Therefore, overcoming the power attenuation caused by free acid generated from EVA in the encapsulation film is a technical problem that urgently needs to be solved in this field.

[0005] It should be noted that the information disclosed in this background section is only for understanding the background technology of this application concept, and therefore, the above description is not considered to constitute prior art information. Summary of the Invention

[0006] This disclosure provides at least one low-power attenuation encapsulating film, its preparation method, and a photovoltaic module.

[0007] In a first aspect, embodiments of this disclosure provide a method for preparing a low-power attenuation encapsulating film, comprising the following steps: S1, mixing inorganic nanomaterials and ethanol at a mass ratio of 1:1.5-2, refluxing at 70-75°C to form solution A, mixing charge dissipation agent and deionized water to form solution B, adding solution B to solution A, simultaneously adding MgCl, heating to 60-80°C, reacting fully, filtering and washing away excess MgCl to obtain charge dissipation agent modified inorganic nanomaterials; S2, mixing EVA matrix resin, charge dissipation agent... In S3, the powder-modified inorganic nanomaterial, silane coupling agent, and initiator are mixed evenly in proportion and mixed at 35-40℃ until complete absorption to obtain the base material; S4, the base material is placed in a granulator and melt-grafted and granulated at 160-250℃, and then granulated after cooling to obtain the grafted anti-PID masterbatch; S5, the grafted anti-PID masterbatch and EVA base material are blended in a certain proportion, and appropriate amounts of initiator, crosslinking agent, light stabilizer, and antioxidant are added. After absorption, the mixture is cast, embossed, cooled, and wound in a screw extruder to obtain a low power attenuation encapsulating film.

[0008] In one optional embodiment, the charge dissipating agent comprises one or more of cationic, anionic, nonionic, zwitterionic, and organometallic complex salts; wherein the cationic type comprises at least one of quaternary ammonium salts and imidazole salts; the anionic type comprises at least one of phosphate ester salts and alkyl sulfonates; the nonionic type comprises at least one of polyethylene oxide and its derivatives, and fatty acid esters / glycerides, wherein the fatty acid esters / glycerides comprise at least one of glyceryl monostearate, ethoxylated fatty amines, and fatty acid monoglycerides; the zwitterionic type comprises alkyl betaines; and the organometallic complex salt comprises at least one of lithium salts and transition metal complexes.

[0009] In one optional embodiment, the EVA matrix resin comprises a high-VA resin and a low-VA resin; wherein the high-VA resin has a VA content of 28-33%, the low-VA resin has a VA content of 15-20%, and the mass ratio of the high-VA resin to the low-VA resin is 5:5-9:1.

[0010] In one alternative embodiment, the silane coupling agent comprises one or more of vinylsilane, methacryloxysilane, and epoxypropoxysilane.

[0011] In one alternative embodiment, the silane coupling agent comprises one or more of vinyltriethoxysilane, vinyltrimethoxysilane, vinyltri(β-methoxyethoxy)silane, methacryloyloxypropyltrimethoxysilane, γ-methacryloyloxypropyltrimethoxysilane, and γ-glycidoxypropyltrimethoxysilane.

[0012] In one alternative embodiment, the inorganic nanomaterial includes at least one of an alkaline oxide precursor and an alkaline oxide.

[0013] In one optional embodiment, the inorganic nanomaterial includes one of magnesium oxide, aluminum oxide, zinc oxide, silicon oxide, zinc acetate, aluminum hydroxide, zinc hydroxide, hydrotalcite, zeolite, and molecular sieve.

[0014] In one alternative embodiment, the initiator comprises any one or a mixture of tert-butyl peroxycarbonate, 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane, 1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, tert-butyl peroxycarbonate-2-ethylhexyl, 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-pentylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-pentylperoxy)cyclohexane, 2,2-bis(tert-butylperoxy)butane, tert-pentyl peroxycarbonate, and tert-butyl peroxy3,3,5-trimethylhexanoate.

[0015] Secondly, this disclosure also provides a low-power attenuation encapsulating film, which is prepared using the method described above.

[0016] Secondly, this disclosure also provides a photovoltaic module, including the low power attenuation encapsulating film as described above.

[0017] The beneficial effects of this invention are that the low-power attenuation encapsulating film and its preparation method graft a charge dissipation agent onto the surface of inorganic nanomaterials through a grafting scheme. The charge dissipation agent modifies the inorganic nanomaterials, which can maximize the melting effect of the resin and form a continuous conductive channel to increase the durability of charge conduction while also having anti-corrosion properties.

[0018] Other features and advantages of the invention will be set forth in the following description, and will be apparent in part from the description, or may be learned by practicing the invention. The objects and other advantages of the invention are realized and obtained through the structures particularly pointed out in the description and the drawings.

[0019] To make the above-mentioned objects, features and advantages of the present invention more apparent and understandable, preferred embodiments are described below in detail with reference to the accompanying drawings. Attached Figure Description

[0020] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.

[0021] Figure 1 An infrared test pattern of charge-dissipating modified silicon dioxide provided in an embodiment of this disclosure;

[0022] Figure 2 This is a schematic diagram of the mechanism of charge dissipation agent grafting modification provided in an embodiment of the present disclosure. Detailed Implementation

[0023] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0024] As used herein, the phrases “in one embodiment,” “according to one embodiment,” “in some embodiments,” etc., generally refer to the fact that a particular feature, structure, or characteristic following the phrase can be included in at least one embodiment of this disclosure. Therefore, a particular feature, structure, or characteristic can be included in more than one embodiment of this disclosure, such that these phrases do not necessarily refer to the same embodiment. As used herein, the terms “example,” “exemplary,” etc., are used to “serve as an example, instance, or illustration.” Any implementation, aspect, or design described herein as “example” or “exemplary” is not necessarily to be construed as preferred or superior to other implementations, aspects, or designs. Rather, the use of the terms “example,” “exemplary,” etc., is intended to present concepts in a specific manner.

[0025] In this document, exemplary embodiments of the present disclosure will be described in more detail with reference to the accompanying drawings. As used herein, expressions such as “at least one of…” modify the entire list of elements when following a list of elements, rather than individual elements in the list. For example, the expression “at least one of a, b, and c” should be understood to include only a, only b, only c, both a and b, both a and c, both b and c, or all of a, b, and c.

[0026] The terminology used herein is for the purpose of describing specific exemplary configurations only and is not intended to be limiting. As used herein, the singular articles “a,” “an,” and “the” may also be intended to include plural forms unless otherwise clearly stated herein. The terms “comprising,” “including,” and “having” are inclusive and thus specify the presence of features, steps, operations, elements, and / or components, but do not preclude the presence or addition of one or more other features, steps, operations, elements, components, and / or combinations thereof. The method steps, processes, and operations described herein should not be construed as requiring them to be performed in the specific order discussed or shown, unless specifically identified as such. Additional or alternative steps may be employed.

[0027] To address the corrosion problem of battery cells, the common approach is to introduce alkaline oxides to neutralize the free acetic acid produced by the aging and hydrolysis of EVA.

[0028] Patent CN114806460A discloses a composite acid suppressor formed by mixing and granulating alkaline metal oxides, carbodiimide and resin, which solves the power loss of components caused by water vapor erosion.

[0029] Patent CN110093112A discloses a method of using a silane coupling agent modified metal hydroxide, metal oxide or metal carbonate as an acid resistant agent to be blended with resin. The modified anti-corrosion additive coats the surface of the metal compound particles with an organic material to reduce their surface energy, so that the metal compound particles are in a stable state, the particles are uniformly dispersed, and the specific surface area is increased compared with the unmodified metal compound particles.

[0030] However, existing solutions that improve the acid resistance of the encapsulant film by directly adding nano-metal oxides or silane-modified nano-metal oxides and delay acid release only slow down module corrosion. They offer little help in mitigating battery power degradation caused by ion migration under the electric field during the PID process.

[0031] In addition, when mixing and extruding by directly adding silane coupling agents, the silane coupling agents in the film are prone to migration and hydrolysis, causing silane failure during wet heat aging and leading to film delamination.

[0032] Finally, the addition of metal hydroxides and metal oxides results in low volume resistivity of the film, making it prone to breakdown and preventing the film from effectively blocking ions and water vapor during the PID process.

[0033] The shortcomings of the above solutions are the result of the inventor's practical experience and careful research. Therefore, the discovery process of the above problems and the solutions proposed in this disclosure below should be considered as the inventor's contribution to this disclosure.

[0034] It should be noted that similar labels and letters in the following figures indicate similar items. Therefore, once an item is defined in one figure, it does not need to be further defined and explained in subsequent figures.

[0035] The following detailed description of some embodiments of the present invention is provided in conjunction with the accompanying drawings. Unless otherwise specified, the following embodiments and features can be combined with each other.

[0036] This disclosure provides a method for preparing a low-power attenuation encapsulating film, comprising the following steps: S1, mixing inorganic nanomaterials and ethanol at a mass ratio of 1:1.5-2, refluxing at 70-75°C to form solution A, mixing a charge dissipation agent and deionized water to form solution B, adding solution B to solution A, simultaneously adding MgCl, heating to 60-80°C, reacting completely, filtering and washing away excess MgCl to obtain charge dissipation agent modified inorganic nanomaterials; S2, mixing EVA matrix resin and charge dissipation agent modified... Inorganic nanomaterials, silane coupling agents, and initiators are mixed evenly in proportion and mixed at 35-40℃ until complete absorption to obtain a base material; S3, the base material is placed in a granulator and melt-grafted and granulated at 160-250℃, and then granulated after cooling to obtain a grafted anti-PID masterbatch; S4, the grafted anti-PID masterbatch and EVA base material are blended in a certain proportion, and appropriate amounts of initiators, crosslinking agents, light stabilizers, and antioxidants are added. After complete absorption, the mixture is cast, embossed, cooled, and wound in a screw extruder to obtain a low-power attenuation encapsulating film.

[0037] Specifically, silane and initiator are introduced into the masterbatch. By controlling the temperature, silane can be grafted in one step. The grafted silane is bonded to the resin, reducing the risk of silane precipitation, improving water resistance, eliminating the need for additional silane addition, improving the peel strength of the film after aging, and reducing the risk of film delamination.

[0038] In some embodiments, specifically, the charge dissipating agent includes one or more of cationic, anionic, nonionic, amphoteric, and organometallic complex salts; wherein the cationic type includes at least one of quaternary ammonium salts and imidazole salts; the anionic type includes at least one of phosphate ester salts and alkyl sulfonates; the nonionic type includes at least one of polyethylene oxide and its derivatives, and fatty acid esters / glycerides, wherein the fatty acid esters / glycerides include at least one of glyceryl monostearate, ethoxylated fatty amines, and fatty acid monoglycerides; the amphoteric type includes alkyl betaines; and the organometallic complex salt includes at least one of lithium salts and transition metal complexes.

[0039] In some embodiments, specifically, the EVA matrix resin includes a high-VA resin and a low-VA resin; wherein the high-VA resin has a VA content of 28-33%, the low-VA resin has a VA content of 15-20%, and the mass ratio of the high-VA resin to the low-VA resin is 5:5-9:1.

[0040] Specifically, by blending the matrix resin and introducing some low-VA resin, the overall acid value release of the film is reduced, the corrosion resistance of the film is improved, the crosslinking density after lamination of the film is further increased, the volume resistivity of the film is increased, and the risk of voltage breakdown in the PID process is reduced.

[0041] In some embodiments, specifically, the silane coupling agent includes one or more of vinylsilane, methacryloxysilane, and epoxypropoxysilane.

[0042] In some embodiments, specifically, the silane coupling agent includes one or more of vinyltriethoxysilane, vinyltrimethoxysilane, vinyltri(β-methoxyethoxy)silane, methacryloyloxypropyltrimethoxysilane, γ-methacryloyloxypropyltrimethoxysilane, and γ-glycidoxypropyltrimethoxysilane.

[0043] In some embodiments, specifically, the inorganic nanomaterial includes at least one of an alkaline oxide precursor and an alkaline oxide.

[0044] In some embodiments, specifically, the inorganic nanomaterials include one of magnesium oxide, aluminum oxide, zinc oxide, silicon oxide, zinc acetate, aluminum hydroxide, zinc hydroxide, hydrotalcite, zeolite, and molecular sieve.

[0045] In some embodiments, specifically, the initiator comprises any one or more of the following: tert-butyl peroxycarbonate, 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane, 1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, tert-butyl peroxycarbonate-2-ethylhexyl, 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-pentylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-pentylperoxy)cyclohexane, 2,2-bis(tert-butylperoxy)butane, tert-pentyl peroxycarbonate, and tert-butyl peroxy3,3,5-trimethylhexanoate.

[0046] This disclosure also provides a low-power attenuation encapsulating film, which is prepared using the method described above.

[0047] This disclosure also provides a photovoltaic module, including the low power attenuation encapsulating film as described above.

[0048] Example 1

[0049] A method for preparing a low-power attenuation encapsulating film includes the following steps:

[0050] S1. Mix 50 parts of EVA matrix resin 2825 (VA:28) and 2020 resin (VA:20), 3 parts of silane coupling agent KH560, 1 part of initiator tert-butyl peroxycarbonate isopropyl ester, and 4 parts of charge dissipation agent carboxymethyl amphoteric imidazoline modified silica material in a certain proportion until the absorption is complete to obtain the base material.

[0051] S2, the base material is placed in a granulator and melt-grafted and granulated at 140-180℃, and then cut into pellets after cooling to obtain grafted anti-PID masterbatch;

[0052] S3 involves blending 5 parts of grafted anti-PID masterbatch and 95 parts of EVA base material 2825 (VA:28), and adding the corresponding amounts of initiator 0.5 parts of tert-butyl percarbonate isopropyl ester, co-crosslinking agent 0.5 parts of trimethylolpropane triacrylate, light stabilizer 0.2 parts of hindered amine 770, and antioxidant 0.2 parts of trioctyl phosphate. After absorption, the mixture is extruded, embossed, cooled, and wound in a screw extruder to obtain a low-power attenuation encapsulating film.

[0053] Example 2

[0054] S1. Mix 50 parts of EVA matrix resin 2825 (VA:28) and 2020 resin (VA:20), 3 parts of silane coupling agent KH560, 1 part of initiator tert-butyl peroxycarbonate isopropyl ester, and 4 parts of charge dissipation agent glyceryl monostearate modified silica material in a certain proportion until the absorption is complete to obtain the base material.

[0055] Steps S2 and S3 are the same as in Example 1.

[0056] Example 3

[0057] S1. Mix 50 parts of EVA matrix resin 2825 (VA:28) and 2020 resin (VA:20), 3 parts of silane coupling agent KH560, 1 part of initiator tert-butyl peroxycarbonate, and 4 parts of charge dissipation agent lauryl ether phosphate modified silica material in a certain proportion until the absorption is complete to obtain the base material.

[0058] Steps S2 and S3 are the same as in Example 1.

[0059] Example 4

[0060] S1, mix 50 parts of EVA matrix resin 2825 (VA:28) and 2020 resin (VA:20), 3 parts of silane coupling agent KH560, 1 part of initiator tert-butyl peroxycarbonate isopropyl ester, and 4 parts of charge dissipation agent dodecyl betaine modified silica material in proportion and mix evenly at 40°C until complete absorption to obtain the base material;

[0061] Steps S2 and S3 are the same as in Example 1.

[0062] Example 5

[0063] S1 and S2 are the same as in Example 1.

[0064] S3, 10 parts of lauryl ether phosphate grafted anti-PID masterbatch and 90 parts of EVA base material 2825 (VA:28) are blended, and the corresponding amounts of initiator 0.5 parts of tert-butyl percarbonate isopropyl ester, co-crosslinking agent 0.5 parts of trimethylolpropane triacrylate, light stabilizer hindered amine 770 0.2 parts of antioxidant trioctyl phosphate are added. After absorption, the film is obtained by casting, embossing, cooling and winding in a screw extruder.

[0065] Example 6

[0066] S1 and S2 are the same as in Example 1.

[0067] S3, 15 parts of lauryl ether phosphate grafted anti-PID masterbatch and 90 parts of EVA base material 2825 (VA:28) are blended, and the corresponding amounts of initiator 0.5 parts of tert-butyl percarbonate isopropyl ester, co-crosslinking agent 0.5 parts of trimethylolpropane triacrylate, light stabilizer hindered amine 770 0.2 parts of antioxidant trioctyl phosphate are added. After absorption, the film is cast, embossed, cooled and wound in a screw extruder to obtain a low power attenuation encapsulating film.

[0068] Comparative Example 1

[0069] The silane coupling agent in step S1 of the embodiment is removed as follows:

[0070] S1. Mix 50 parts of EVA matrix resin 2825 (VA:28) and 2020 resin (VA:20), 1 part of initiator tert-butyl peroxycarbonate isopropyl ester, and 4 parts of charge dissipation agent lauryl ether phosphate modified silica material in a certain proportion until the absorption is complete to obtain the base material.

[0071] S2 and S3 are the same as in Example 1

[0072] Comparative Example 2

[0073] The low-VA resin in step S1 of the embodiment was removed as follows:

[0074] S1. Mix 100 parts of EVA matrix resin 2825 (VA:28) resin, 3 parts of silane coupling agent KH560, 1 part of initiator tert-butyl peroxycarbonate isopropyl ester, and 4 parts of charge dissipation agent lauryl ether phosphate modified silica material in proportion and mix evenly at 40°C until complete absorption to obtain the base material.

[0075] S2 and S3 are the same as in Example 1

[0076] Comparative Example 3

[0077] The charge dissipating agent in step S1 of the embodiment is removed as follows:

[0078] 50 parts of EVA matrix resin 2825 (VA:28) and 2020 resin (VA:20), 3 parts of silane coupling agent KH560 and 1 part of initiator tert-butyl peroxycarbonate are mixed evenly in proportion and mixed at 40°C until complete absorption to obtain the base material.

[0079] S2 and S3 are the same as in Example 1

[0080]

[0081] Please see Figure 1 and Figure 2 ,Depend on Figure 1 and Figure 2 It can be seen that the surface of the grafted nanomaterial exhibits stretching vibration peaks of P=O and -CH2 / -CH3, which belong to the charge dissipation agent. The grafted charge dissipation agent can form a continuous conductive channel and act on the encapsulation film to improve its anti-attenuation effect.

[0082] In summary, this low-power attenuation encapsulating film and its preparation method graft a charge dissipation agent onto the surface of inorganic nanomaterials using a grafting scheme. The charge dissipation agent modifies the inorganic nanomaterials, which can maximize the melting effect of the resin and form a continuous conductive channel to increase the durability of charge conduction while also providing corrosion resistance.

[0083] Based on the above-described preferred embodiments of the present invention, and through the foregoing description, those skilled in the art can make various changes and modifications without departing from the inventive concept. The technical scope of this invention is not limited to the contents of the specification, but must be determined according to the scope of the claims.

Claims

1. A method for preparing a low-power attenuation encapsulating film, characterized in that, Includes the following steps: S1. Inorganic nanomaterials and ethanol are mixed evenly at a mass ratio of 1:1.5 to 2 and refluxed at 70 to 75°C to form solution A. Charge dissipation agent and deionized water are mixed to form solution B. Solution B is added to solution A, and MgCl is added at the same time. The temperature is raised to 60 to 75°C. After the reaction is complete, the excess MgCl is washed by filtration to obtain charge dissipation agent modified inorganic nanomaterials. S2, EVA matrix resin, charge dissipation agent modified inorganic nanomaterial, silane coupling agent and initiator are mixed evenly in proportion, and mixed at 35-40℃ until complete absorption to obtain the base material; S3, place the base material in a granulator and melt-graft granulate at 160-250℃, then cut into pellets after cooling to obtain grafted anti-PID masterbatch; S4 involves blending grafted anti-PID masterbatch and EVA base material in a certain proportion, and adding appropriate amounts of initiator, crosslinking agent, light stabilizer, and antioxidant. After absorption, the mixture is extruded, embossed, cooled, and wound in a screw extruder to obtain a low-power attenuation encapsulating film.

2. The preparation method according to claim 1, characterized in that, The charge dissipating agent includes one or more of cationic, anionic, nonionic, amphoteric, and organometallic complex salts; wherein The cationic type includes at least one of quaternary ammonium salts and imidazole salts; The anionic type includes at least one of phosphate salts and alkyl sulfonates; The nonionic type includes at least one of polyethylene oxide and its derivatives, and fatty acid esters / glycerides, wherein the fatty acid esters / glycerides include at least one of glyceryl monostearate, ethoxylated fatty amines, and fatty acid monoglycerides; The zwitterionic type includes alkyl betaines; The organometallic complex salts include at least one of lithium salts and transition metal complexes.

3. The preparation method according to claim 1, characterized in that, The EVA matrix resin includes high VA resin and low VA resin; The high-VA resin has a VA content of 28-33%, the low-VA resin has a VA content of 15-20%, and the mass ratio of the high-VA resin to the low-VA resin is 5:5-9:

1.

4. The preparation method according to claim 1, characterized in that, The silane coupling agent includes one or more of vinylsilane, methacryloxysilane, and epoxypropoxysilane.

5. The preparation method according to claim 4, characterized in that, The silane coupling agent includes one or more of vinyltriethoxysilane, vinyltrimethoxysilane, vinyltri(β-methoxyethoxy)silane, methacryloyloxypropyltrimethoxysilane, γ-methacryloyloxypropyltrimethoxysilane, and γ-glycidoxypropyltrimethoxysilane.

6. The preparation method according to claim 1, characterized in that, The inorganic nanomaterials include at least one of basic oxide precursors and basic oxides.

7. The preparation method according to claim 6, characterized in that, The inorganic nanomaterials include one of the following: magnesium oxide, aluminum oxide, zinc oxide, silicon oxide, zinc acetate, aluminum hydroxide, zinc hydroxide, hydrotalcite, zeolite, and molecular sieve.

8. The preparation method according to claim 1, characterized in that, The initiator comprises any one or a mixture of tert-butyl peroxycarbonate, 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane, 1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, tert-butyl peroxycarbonate-2-ethylhexyl, 2,5-dimethyl-2,5-bis(tert-butylperoxy)hexane, 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-pentylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-pentylperoxy)cyclohexane, 2,2-bis(tert-butylperoxy)butane, tert-pentyl peroxycarbonate, and tert-butyl peroxide.

9. A low-power attenuation encapsulating film, characterized in that, It is prepared by the method described in any one of claims 1-8.

10. A photovoltaic module, characterized in that, Including the low power attenuation encapsulating film as described in claim 9.

Citation Information

Patent Citations

  • Anticorrosive photovoltaic packaging material EVA adhesive film and preparation method thereof

    CN110093112A